(untitled) (Research, Society and Development, 2025)
Parkinson’s Disease (PD) is a progressive neurodegenerative condition that affects millions worldwide, marked by motor and non-motor symptoms resulting from the loss of dopaminergic neurons. While medications like levodopa are initially effective, long-term use may lead to motor complications. Deep Brain Stimulation (DBS) has emerged as a therapeutic alternative for refractory cases, acting through modulation of specific neural circuits. This narrative review analyzed three studies published between 2020 and 2024 comparing DBS and pharmacological treatment in PD. Findings indicate that DBS, particularly when targeting the subthalamic nucleus (STN) or internal globus pallidus (GPi), significantly increases “on” time without dyskinesias, improves quality of life, and allows up to a 65% reduction in levodopa dosage. These motor benefits can persist for up to 10 years, although non-motor symptoms may continue to progress. DBS has no neuroprotective effect but shows long-term cost-effectiveness, especially when applied early. Careful patient selection is crucial, taking into account factors such as age, levodopa response, and cognitive or psychiatric comorbidities, due to possible surgical and neuropsychiatric complications. While DBS does not alter disease progression, it has a significant functional impact and may benefit in the future from adaptive systems based on neural biomarkers. In conclusion, DBS proves superior to medication alone in advanced PD for motor symptom control and quality of life, underscoring the need for further studies on its personalized use and combination with disease-modifying therapies.